LEGAL REMEDY ON THE REVOCATION OF FORECLOSURE SALE OF HYPOTHECATION THROUGH COAL CONSUMER DISPUTE SETTLEMENT BOARD (A Case Study on the Ruling No. 1061 K/Pdt.BPSK/2016) - AYU ULINA SIAHAAN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Muhamamd Yamin2. Sunarmi3. Sutiarnoto Article 27 of the Directive of the Minister of Finance No. 27/PMK/065/2016on Guidelines for Implementing an Auction states that an auction can be revokedonly when it is asked by the seller or by the Court’s verdict. There is a problem asfollows: Syahbuddin Purba, through the Consumer Dispute Settlement Board ofCoal’s Ruling No. 126/P3K/JS-III/BPSK-BB/IV/2016, revoked foreclosure sale ofhypothecation. The research problems are how about the revocation of foreclosuresale of hypothecation for realizing legal protection, how about the authority of BPSKof Coal to revoke the foreclosure sale of hypothecation, and how about legal remedyof the revocation of auction to the buyer based on BPSK of Coal’s Ruling.The research used juridical normative and descriptive analytic method.Primary data were gathered by conducting interviews and secondary data consistedof Law No. 4/1996 on Hypothecation on Land and Anything Found on It, theDirective of the Minister of Finance No. 27/PMK/065/2016 on Guidelines forImplementing Auction, Law No 8/1999 on Consumer Protection, and the DirectiveNo. 1061 K/Pdt.Sus-BPSK/2016. Secondary legal material consisted of books, andtertiary legal material consisted of dictionary and dictionary of jurisprudence.The result of the research showed that revocation on foreclosure sale ofhypothecation can be revoked when it does not comply with legal provisions, theauction does not meet Article 1320 of the Civil Code, the buyer is foreign citizen ormixed marriage based on Article 21 in conjunction with Article 28 of Law ofAgrarian Affairs. The authority of BPSK is merely to impose on compensation on thedamage, pollution, and/or consumer’s loss as the result of consuming the goodsand/or using business people’s service so that revocation cannot be done. Legalremedy for revoking foreclosure sale of hypothecation to buyers through the Rulingof BPSK of Coal No.126/P3K/JS-III/BPSK-BB/IV/2016 cannot be done because theregulation on the revocation of a credit contract which becomes the ground for prateexecution right has to be through District Court’s verdict and not through the Rulingof BPSK so that Syahbudin Purba should do legal remedy through litigation.Keywords: Revocation, Auction, Consumer Dispute Settlement Board